Occupational Physical Activity Was Associated With Disability Levels at 6-Month Follow-Up of Patients With Chronic Nonspecific Low Back Pain: A Prospective Cohort Study - Hisamatsu, Thalysi M. [UNESP]; Oliveira, Crystian B. [UNESP]; Lira, Fábio S. [UNESP]; Morelhão, Priscila K.; Azevedo, Bruna R. [UNESP]; Lemes, Ítalo R.; Franco, Márcia R.; Pinto, Rafael Z. (Human Kinetics, 2022)
Background: Physical activity plays an important role in the prognosis of chronic low back pain (LBP); however, whether physical activity predicts pain intensity and disability remains unknown. This study investigated whether objective and subjective physical activity measures predict pain intensity and disability levels 6 months later in patients with chronic LBP. Methods: Patients with chronic LBP seeking care at 2 outpatient physiotherapy clinics were recruited. At baseline assessment, we collected anthropometric/sociodemographic data, duration of symptoms, pain intensity, disability, and physical activity (accelerometer and questionnaire). After 6 months, we reassessed pain and disability. Multivariable regression analyses were performed to investigate the association of physical activity measures with pain and disability at follow-up. Results: A total of 179 patients with chronic LBP were included. High occupational physical activity at baseline predicted disability at 6-month follow-up (B = 1.22; 95% confidence interval, 0.21 to 2.21) after controlling for age and baseline disability, meaning that for every 1-point increase in occupational physical activity, disability increased on average by 1.22 point. The remaining physical activity measures showed no association with pain intensity or disability at follow-up. Conclusion: Higher perceived levels of occupational physical activity predicted higher disability levels at 6-month follow-up in patients with chronic LBP.
Keywords: exercise; musculoskeletal pain; outcome measurement; prognosis